Evaluation of 850°C Heat Treatment: Effects of Used-Oil Quenching, Brine Quenching, and Pack Carburizing on the Rockwell Hardness of ST37 Shredder Blades - Fajrul, Rahmat; Setyawan, Reinaldi Teguh; Ahmad, Zaid; Gunawan, Gunawan (Jurnal Mekanik Terapan, 2026)
Waste shredder blades operate under abrasive contact and intermittent impacts from heterogeneous materials, making surface hardness a key property for maintaining cutting performance and reducing premature dulling. This study evaluates the effect of a 850°C heat-treatment route on the hardness of ST37 low-carbon steel used for shredder-blade applications. Plate specimens (100 mm × 100 mm × 10 mm) were prepared and tested under four conditions: untreated (as-received), pack carburizing using coconut-shell charcoal followed by furnace cooling, quenching in used oil, and quenching in saltwater (brine). Hardness was measured using the Rockwell C method (ASTM E18) with a diamond cone indenter (10 kgf minor load and 150 kgf major load). For each condition, ten hardness readings were collected and analyzed using one-way ANOVA (α = 0.05).The untreated specimens yielded an average hardness of 83.85 HRC. The pack-carburized and furnace-cooled condition resulted in a substantial decrease to 69.35 HRC, accompanied by higher variability, indicating a less favorable hardness response under the applied cooling route. In contrast, quenching after heating at 850°C increased hardness to 85.55 HRC for used-oil quenching and 88.35 HRC for brine quenching, with brine showing the highest mean value but also a wider scatter. ANOVA confirmed that the treatment route significantly influenced hardness (p < 0.05). Overall, the results indicate that, under the present parameters, quenching routes are more effective than the pack carburizing + furnace cooling route for improving blade hardness, while process consistency is important to control hardness dispersion, particularly for brine quenching.